S132 Airway dysfunction and inflammation in pool and non-pool based elite endurance athletes. (16th November 2010) - Martin, N; Lindley, M R; Hargadon, B; Monteiro, W; Pavord, I D
Abstract : Introduction: Previous studies have suggested that eosinophilic airway inflammation is common in elite swimmers; the chemical pool environment often blamed. We set out to address this question in a cross-sectional study of 109 international athletes from a variety of sporting backgrounds. Methods: All had symptoms suggesting exercise-induced asthma and were either inhaled corticosteroid naïve or withdrew these for >4 weeks. β2 -agonists, exercise and caffeine were withheld for 8 h prior to testing. Symptoms were assessed using the Juniper ACQ, airways dysfunction using the eucapnic voluntary hyperventilation (EVH) test and airways inflammation using exhaled nitric oxide (FENO ) and induced sputum eosinophil % (eos). Athletes were classed as pool based if they exercised in an indoor pool environment for >5 h per week, and non-pool based if they exercised in a pool for <1/2 h per week. Results: Demographic details were similar. Mean (±SEM) % fall in FEV1 post EVH was 18.96±1.701 (n=47) in pool and 11.39±1.249 (n=62) in non-pool athletes (mean difference 7.569; 95% CI 3.480 to 11.66; p=0.0004), 76% of pool and 39% of non-pool athletes had a positive test (>10% fall). The geometric mean (log SD) eos (pool 2.667 (0.797)), non-pool 3.060 (0.867), p=0.802), and FENO (pool 25.05 (1.570), non-pool 28.06 (1.475) ppb, p=0.914) was no different between groups; 14.9% of pool and 12.9% of non-pool athletes had eos >3%. % fall in FEV1 had good correlation with log eos (r=0.551, p<0.0001); a 25% fall being the optimum (AUC 0.89, p<0.0001, sens 79%, spec 93%). Log FENO and log eos correlated strongly (r=0.644, p<0.0001); FENO of >47 being most predictive of eos>3% (AUC 0.912, p<0.0001, sens 78%, spec 92%). Symptoms correlated poorly with either airways dysfunction or inflammation. Conclusions: Individual athletes with symptoms vary markedly in the levels of airways dysfunction and inflammation expressed. There is more airway dysfunction in pool athletes but not more eosinophilic airways inflammation suggesting that the pool environment if anything predisposes to airways dysfunction. Exhaled nitric oxide is a promising non-invasive means of assessing eosinophilic airways inflammation in all elite athletes.